Literature Review on the Implementation of Blockchain Technology for Supply Chain Transparency and Security - Aisyah Chayani; Hidayatul Ikhsan (Engineering and Technology International Journal, 2025)
The digital transformation of supply chain systems has intensified the demand for greater transparency and data security. Blockchain technology emerges as an innovative solution, offering distributed, immutable, and verifiable data recording accessible in real time by all stakeholders. This study aims to systematically analyze previous research on the application of blockchain technology in supply chain management, with a particular focus on transparency and security aspects. A systematic literature review (SLR) approach was employed, comprising three main stages: planning, literature selection, and result reporting. From an initial pool of 200 articles, six were identified as meeting the inclusion criteria and were further analyzed. The findings reveal that blockchain enhances product traceability, strengthens data integrity, and reduces dependency on intermediaries. However, its implementation still faces several challenges, including infrastructure limitations, regulatory uncertainties, and a lack of understanding among industry actors. This review contributes to both academic and practical knowledge by highlighting the potential benefits and key obstacles of adopting blockchain in modern supply chain management.